Printing on the Archives of Sultan Syarif Kasim II - Idayanti, Iik; Jefrizal, Jefrizal; Afriadi, Deni (Universitas Negeri Padang, 2023)
This article reviews the printers listed in the archives left by Sultan Syarif Kasim II (SSK II). SSK II has many archives that are currently stored in the palace of the Siak Sultanate. Part of the archive is handwritten, typed and printed. Types of printed manuscripts are quite interesting to discuss because there are names of printing companies. In the 19-20 centuries, the Colonial Government controlled the printing sector. They dominated the development of the print world and exercised strict supervision. The research results showed that there were seven printers in the archives of Sultan Syarif Kasim II, including Batavia Landsdrukkerij, De unie Weltevreden, Stoomsnelpersdrukkerij van H. M. Van Dorp & Co. Batavia, Typ. Courant Deli, Typ. Drukkerij Batak, Typ. Limbago Pajakoemboeh, and Typ. Varekamp & Co., Medan. The link between the Siak Sultanate and all publications and contents of documents shows that all government activities must be under supervision and permits are required in the implementation process.